Preliminary Memorandum on the Fourth Five Year Plan of Himachal Pradesh - Planning Commission (Planning Commission, 1965)
This preliminary memorandum, which is to be read in continuation of the Draft Perspective Plan and the Draft Fourth Five Year plan, already submitted to the Planning Commission, is, as its very title indicates, merely a preliminary phase of the preparation of the Fourth Five Year Plan. The Draft Perspective Han as well as the Draft Fourth Five Year Plan of Himachal Pradesh has still to be considered by the Council of Ministers, and the preliminary memorandum is to be treated in that light, and as a very tentative embodiment of Himachal Pradesh’s Draft Fourth Five Year Plan.
Government of Himachal Pradesh